Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Keputusan Menabung di BMT Mazaya - Febiyanti, Adela Ika; Wahyudi, Agung (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
The aim of this research is to find out how the quality of tangible service, emphaty, responsiveness, reliability,assurance and trust influence saving decisions. The study used a random sampling method of 55 BMT Mazaya respondents. Primary data is collected using a Google Form questionnaire with a Likert scale. Tests used include validity, reliability, normality, heterocadastisity, multicolinearity, partial itest i(t itest), isimultaneous itest i(f itest), idouble linear iregression ianalysis, iand idetermination icoefficient itest i(R2). Research results show that high-quality service elements, including tangible, emphaty, reliability, and assurance, influence saving decisions, but responsiveness does not. Confidence affects savings decisions at BMT Mazaya.